Welsh Labour: From “Fantastic Results” in June 2017 to the “Crumbling of the Red Wall” in December 2019 - Stéphanie Bory (Revue Française de Civilisation Britannique, 2020)
In November 2019, the British Parliament finally agreed to decide the holding of general elections in the United Kingdom, only 18 months after the previous ones. If the Welsh Labour Party, chaired by a new leader, Mark Drakeford, since December 2018 and weakened by the May 2019 European Elections, managed to remain the dominant party in the country, it obtained its worst election results since 1935, which can be explained by its weak leadership and the confusing message sent to voters. Such results are a bad omen for the forthcoming Welsh Parliament election scheduled in May 2021.